Multivariable friction compensation control for a variable stiffness actuator. (January 2017) - Misgeld, Berno J.E.; Kramer, Matthias; Leonhardt, Steffen
Abstract: A novel decentralised friction compensation control approach for a specific electro-pneumatic adjustable impedance actuator (EPAIA) is presented in this paper. EPAIA employs a rotary pneumatic actuator to provide an adjustable compliant element in series to the gear train. The compliant element is thereby inserted between a brushless direct current motor, a gear reduction and the load. The decentralised control system consists of two control-loops and a decoupler. In a first control-loop, the interaction torque between actuator and load is controlled with a cascaded/post-compensator architecture involving a norm-optimal strictly positive-real H 2 -controller to minimise the actuator output impedance. In a second control-loop, a stiffness controller continuously adjusts the pressure of the pneumatic chambers to realise a certain interaction stiffness. Since first hardware validation tests identified the occurrence of nonlinear friction effects that worsened the control performance, the control strategy has been extended with a new adaptive friction compensation scheme. This approach is based on the two-state dynamic friction model with elasto-plasticity (2SEP) for which an Extended Kalman Filter (EKF) friction observer has been developed and incorporated to the decentralised control strategy. The resulting overall controller has been validated in nonlinear simulations and in a test bench under variable load conditions.